2020
DOI: 10.5114/aoms.2020.101243
|View full text |Cite
|
Sign up to set email alerts
|

Anti-tumor effects of isoliquiritigenin in Bcl-2/Bax and PCNA expression of T24 human bladder cancer cells

Abstract: IntroductionThe aim of this study was to investigate the proliferation and apoptosis of T24 after treatment with isoliquiritigenin (ISL) and to explore the underlying mechanism.Material and methodsT24 cells were divided into 6 groups and cultured. The five experimental groups were seeded into medium with 10, 20, 40, 80, and 160 µM ISL and the control group was administered with 0.01% DMSO. The cell morphology was observed using an optical microscope. The proliferation of cells and half maximal inhibitory conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Furthermore, ISL upregulated pro-apoptotic protein expression (e.g., Bax, Bim, Apaf-1, caspase-9 and caspase-3) and downregulated expression of the antiapoptotic Bcl-2 protein, decreased mitochondrial membrane potential and increased cyclin dependent kinase 2 activity [ 308 ]. Later, Huang et al [ 309 ] reported that ISL caused arrest of cell cycle at G1 phase in T24 cells. It also significantly reduced cell migration and downregulated expression of proliferating cell nuclear antigen, which plays a role in cell transition from G1 phase to S phase.…”
Section: Chalcones and Bladder Cancermentioning
confidence: 99%
“…Furthermore, ISL upregulated pro-apoptotic protein expression (e.g., Bax, Bim, Apaf-1, caspase-9 and caspase-3) and downregulated expression of the antiapoptotic Bcl-2 protein, decreased mitochondrial membrane potential and increased cyclin dependent kinase 2 activity [ 308 ]. Later, Huang et al [ 309 ] reported that ISL caused arrest of cell cycle at G1 phase in T24 cells. It also significantly reduced cell migration and downregulated expression of proliferating cell nuclear antigen, which plays a role in cell transition from G1 phase to S phase.…”
Section: Chalcones and Bladder Cancermentioning
confidence: 99%